ISLAMIC BUSINESS ETHICS IN THE MAQASID AL-SHARI'AH PERSPECTIVE - Hani Sholihah (Univeristas Islam Bandung, 2020)
Various studies on business ethics have carried out. However, as a Muslim, legal awareness of business ethics implementation will be more easily enhanced by using the Islamic Law approach, including the maqasid al-shari'ah plan. This research is library research, which uses qualitative methods with a juridical (legal) approach, namely Islamic Law. The results showed that in terms of maqasid al-shari'ah, the principles of Islamic business ethics were in line with maqasid al-shari'ah. The principle of the oneness of Allah (monotheism): hifzh al-din (guarding religion); the principle of balance and justice, related to hifzh al-nafs (guarding the soul); the principle of freedom is in line with hifzh al-ʻaql; the law of responsibility following hifzh al-nasl (safeguarding offspring and h